2005
DOI: 10.1111/j.1742-1241.2005.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume in patients with obesity

Abstract: Mean platelet volume (MPV), a determinant of platelet function, is a newly emerging risk factor for atherothrombosis. The present study was designed to evaluate MPV in patients with obesity compared with non-obese control subjects. We selected 100 non-obese subjects and 100 subjects with obesity [body mass index (BMI) > or =30 kg/m(2)] matched for age and gender. The MPV was significantly higher in obese group than in non-obese control group (10.3 +/- 1.2 vs. 9.0 +/- 0.8 fl, p < 0.01). MPV was positively corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
161
10
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(193 citation statements)
references
References 13 publications
13
161
10
9
Order By: Relevance
“…BMI is a strong and independent risk factor for both venous and arterial thrombosis [3], and obese individuals are reported to have higher MPV than non-obese controls [22]. Even after adjustments for age, sex, smoking, BMI and platelet count in the multivariable model, MPV remained a risk factor for VTE in our study.…”
Section: Discussionmentioning
confidence: 47%
“…BMI is a strong and independent risk factor for both venous and arterial thrombosis [3], and obese individuals are reported to have higher MPV than non-obese controls [22]. Even after adjustments for age, sex, smoking, BMI and platelet count in the multivariable model, MPV remained a risk factor for VTE in our study.…”
Section: Discussionmentioning
confidence: 47%
“…Obese individuals have elevated MPV values. 23 Elevated MPV values have also been reported to correlate with a higher prevalence of metabolic syndrome. 24 In the present investigation, positive correlations were found between MPV and the prevalence of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Mean platelet volume has been studied in many vascular diseases. Platelets play a pivotal role in atherothrombosis, the major cause of most unstable coronary syndromes and increased MPV levels have been shown as an indicator in myocardial infarcts [4,[11][12][13], congestive heart disease [13], cerebrovascular diseases [14], obesity [15] and hypertensive patients [16,17]. There is a previous study that suggested a relationship between high MPV levels and an increase in the frequency of restenosis in patients who received coronary angioplasty [18].…”
Section: Discussionmentioning
confidence: 99%